2016
DOI: 10.1111/jcmm.13016
|View full text |Cite
|
Sign up to set email alerts
|

Repeated otilonium bromide administration prevents neurotransmitter changes in colon of rats underwent to wrap restraint stress

Abstract: Otilonium bromide (OB) is a spasmolytic drug successfully used for the treatment of irritable bowel syndrome (IBS). Its efficacy has been attributed to the block of L‐ and T‐type Ca2+ channels and muscarinic and tachykinin receptors in the smooth muscle. Furthermore, in healthy rats, repeated OB administration modified neurotransmitter expression and function suggesting other mechanisms of action. On this basis, we investigated whether repeated OB treatment prevented the functional and neurochemical changes ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…The efficacy of this test is confirmed by the development of an immediate hyperalgesia [18], the inhibition of small intestinal transit, the stimulation of large intestinal activity and the incidence of an increased fecal excretion [15]. Also, it was recently demonstrated that rats underwent testing to the restrain stress presented a low-grade mucosal inflammation, with a significant increase in mast cells and eosinophilic granulocytes [19,20], that is seen to have overlapped on what is described in colonic biopsies of IBS patients [21].…”
Section: Discussionmentioning
confidence: 93%
“…The efficacy of this test is confirmed by the development of an immediate hyperalgesia [18], the inhibition of small intestinal transit, the stimulation of large intestinal activity and the incidence of an increased fecal excretion [15]. Also, it was recently demonstrated that rats underwent testing to the restrain stress presented a low-grade mucosal inflammation, with a significant increase in mast cells and eosinophilic granulocytes [19,20], that is seen to have overlapped on what is described in colonic biopsies of IBS patients [21].…”
Section: Discussionmentioning
confidence: 93%
“…Probably thanks to this multi-target activity, OB effectively reduced pain and improved defecation alterations in placebo-controlled trials in IBS patients (71). Conversely, OB tested in experimental models of visceral sensitivity, at least in WRS, was less active as compared to the other agents previously reviewed (20). Another antispasmodic such as pinaverium bromide endowed with L-type calcium channel blocker and antimuscarinic activity improved motility disorders and consequently reduced stool problems in IBS patients.…”
Section: Calcium Channelsmentioning
confidence: 97%
“…The efficacy of this test is confirmed by the development of an immediate hyperalgesia, quantifiable in colon-rectal distention (CRD) number (18), the inhibition of small intestinal transit, the stimulation of large intestinal activity and increased fecal excretion (17). We recently demonstrated that rats underwent to the WRS presented a low-grade mucosal inflammation with a significant increase in mast cells and eosinophylic granulocytes (19,20) that overlapped that described in colonic biopsies of IBS (21). Moreover, these animals showed important changes in the glial cells, in inhibitory and excitatory neurotransmitters and receptors that were interpreted as responsible for the dysmotility and hypersensitivity present in IBS patients.…”
Section: The Wrap Restrain Stress (Wrs)mentioning
confidence: 99%
See 2 more Smart Citations